Spaces of social with solidarity economy? The case of the Movement of the homeless Metropolitan and of Peru - Fonseca Zanca, Daniel (2017)
The paper deals with the existence of relations of social and solidarity economy within the Movement of the Homeless Metropolitan and Peru (MST-MP). This movement arises from the right to housing in the city of Lima and within the long historical process of land occupations occurred as part of the development of peripheral areas of various cities. The work analyzes four main themes: history and memory of the experience, organization and internal conflicts, relationship with actors of their environment and future prospects.